Elucidation of aqueous alteration in the lava units with nakhlites NWA 10153 and NWA 6148 - Kukihara, Kakeru; Miyahara, Masaaki; Yamaguchi, Akira; Takahashi, Yoshio; Takeichi, Yasuo; Tomioka, Naotaka; Ohtani, Eiji (2022)
The 13th Symposium on Polar Science/Ordinary sessions [OA] Antarctic meteorites, Thu. 17 Nov. conference object